Communitarianism, Personhood and Politics: Engaging with the Philosophy of Bernard Matolino (Guest Editor’s Introduction) - Mutshidzi MARAGANEDZHA (Arụmarụka)
This special issue aims to investigate the complex landscape of communitarianism in African philosophy, with a particular focus on the heated debates surrounding radical, moderate, and limited communitarianism. At the heart of this project lies an in-depth exploration of Bernard Matolino’s influential ideas and their significance within the African philosophical tradition. We will investigate how Matolino’s work has informed contemporary African thinkers as they redefine the role of community in modern, multicultural societies. This involves navigating the intricate relationships between community, identity, social cohesion, and individual rights and examining the ethical and political implications of communitarianism in these contexts. By examining the intersections of communitarian thought and African social realities, we aim to provide a nuanced understanding of how community shapes individual and collective experiences in Africa.